ANALYSIS OF THE OPPORTUNITY TO EXTEND THE OPERATION OF THE INTERMEDIATE PRESSURE ROTOR WITH CRITICAL SIZE CRACKS - Chernousenko, Olga Yuriivna; Rindyuk, Dmitro Viktorovich; Peshko, Vitaliy Anatoliyovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2020)
The paper shows the validity of the re-extension of operation-time of the intermediate pressure rotor of the K-200-130-3 turbine unit number 9 of the Luhansk TPP, with taking into account the critical size of the cracks that arose during the exploitation period. It was considered the conduct and results of several studies that were aimed to analyze the possibility of extending the operation-time of the equipment after conducting grooving of different depths radial grooves in places of cracks arising. The forecast of the possibility of continuation of cracks in the grooves is also provided. For justification of the possibility of further operation of the intermediate-pressure rotor of the turbine, computational experiments were carried out. Methods of mathematical modeling were used to determine the thermal, strain-stress state and long-term strength of the investigated object. The boundary value problem of non-stationary thermal conductivity for the stationary and main launch modes of the steam turbine installation is solved. The sampling of the calculated area is based on the finite element method. The calculation of the strain-stress state of the intermediate pressure rotor is made by the joint action of temperature stresses, temperature field gradients, centrifugal forces of inertia and stresses from pressure. It has been established, that when working in semi-peak modes, it is possible to increase the residual service life-time after carrying out constructive-repair measures, namely, cutting metal surface layer of thermal grooves to the admissible value. Cutting metal of the surface layer of intermediate-pressure rotor thermal grooves of 18 mm gives an opportunity to increase the residual service life-time and extend the exploitation. Also, on a concrete example, it has been proven inexpedient to deep, more than 18 mm, cutting metal into thermal grooves.